Franco Pastori, Eclectic Jurist and Great Teacher: Peer-reviewed article (Italian Review of Legal History, 2022)
Franco Pastori (1923-2003) graduated in Law at the University of Milan after the end of the Second World War, with a thesis in Roman Law entitled Intorno all’evoluzione storica della sponsio romana, supervisor Gaetano Scherillo, of whom he soon became an assistant. Pastori began his activity as a university professor in Urbino and obtained the title of full professor in 1959; after a few years of teaching in Parma, since 1972 for decades he taught Roman Law and Institutions of Roman Law at the Milanese university, also covering for a long time the positions of director of the Institute of Roman Law and president of the Opera Universitaria, then ISU - Institute for University Study -. A highly effective teacher, a jurist with multiple interests, he published various essays, especially on very demanding subjects of Roman Private Law, particularly on the concept of obligation, on verbal contract, on commodatum and on superficies. The second paragraph of this study lists Pastori’s works on commodatum an re-exposes in broad outline the theses he elaborated. We owe to Franco Pastori an original vision of synthesis, in the historical and dogmatic profile, of the institution of gratuitous loan for use, which arose as a mere relationship of social pratice, then was legally recognized as a result of the intervention of the praetor and gradually subjected to a long interpretative development by jurisprudence, through a historical evolution that began in the first century BC and completed in the works of Byzantine authors. In the formulary procedure the lender’s reasons were first protected with a formula in factum, aimed at sanctioning only the non-return of the thing, and then also with a formula in ius concepta introduced with reference to the obligations not to deteriorate the thing and to comply with the use of the same within the limits established by contract. According to Pastori, the formula in factum would have continued to be applied in cases of non-return of the thing given on loan even after the introduction of the broader formula in ius because it provided for an objective responsibility, for custodia, of the borrower, so that the lender often had an interest to act judicially with that formula, which attributed the sole burden of proving that the thing had not been returned to him, rather than with the more recent formula in ius of good faith. The circumstance would also explain the insertion of the actio commodati in the praetorian Edict alongside mutuum and condictiones instead of among the bonae fidei iudicia, unlike deposit, a real contract equally protected by two formulas and in various respects similar to commodatum, but in which on the basis of the formula in factum the depositee was liable only for dolus (given that the relationship is mostly in the almost exclusive interest of the depositor), so that the introduction of the formula in ius ex fide bona deprived it of any pratical utility. With the same reasons Pastori also motivated the presence of the iudicium depositi and the absence of the iudicium commodati in Gai. 4.62’s list of good faith actions.As for the tools for the protection of the borrower’s reasons, an ius retentionis of the thing given in loan is attested, in the event of necessary expenses paid in order to preserve it; a compensatio, for the damages suffered; and a special actio granted to him, qualified as contraria in opposition to that granted to the lender.In dealing with commodatum, Pastori also took a stand on very complex and debated issues of a more general nature, such as the elaboration of the concept of culpa by Roman jurisprudence and the evolution of the criteria for imputing contractual liability.In the third paragraph of the article, the opinions of the Authors who dealt with commodatum after Franco Pastori - even in recent years - are quickly reviewed, especially in order to assess the impact that his works had on Roman Law doctrine. In general, although with several differences between individual Scholars, only some of his theses have been accepted: but Pastori’s studies have been constantly recognized as an essential point of reference for the reconstruction of the institute. The next paragraph presents the institutional manual that Franco Pastori wrote patiently collecting the content of his lectures: Gli istituti romanistici come storia e vita del diritto, published for the first time in 1986 and subsequently gradually integrated with following editions, until to come to deal comprehensively with Roman Private Law, both in the various epochs in which it had value as a positive law, and as the ideal foundation of Western legal thought and civilizations. From this work, which constitutes a sort of “spiritual testament” of Pastori, but moregenerally from his publications and even more from his lessons, his ability to highlight and enhance the profound heritage transmitted from the Roman age to modern Law emerges: undoubtedly a distinctive feature of his scientific activity. The last part of the essay also aims to recall some other aspects of his rich personality, as it was manifested in daily life, among professional commitments, research and teaching.
Keywords: Roman Law as the foundation of current Law in Franco Pastori’s thought; Commodato contratto responsabilità; formula in factum and formula in ius to protect commodatum; Gli istituti romanistici come storia e vita del diritto; the modernity of Roman Law